How Data Governance optimizes cost and increases trust in data - Petrák, Jakub (2022)
This thesis analyzes how Data Governance capabilities can enable business users to access high-quality data, optimize cost and increase trust in data. The data for this thesis was collected from an existing Amazon cloud environment and through business user surveys. New solution designs were proposed, implemented, and results were compared with the initial as-is analysis. In addition, a new user experience platform (Data Marketplace) was created with Informatica services with a web-based user interface. The results show annual cost savings of 260 thousand of US dollars. New solution designs and development standards mainly drive cost efficiency. In addition, new data quality capabilities were implemented and are actively measured. As a result, the overall user trust in data, data quality visibility, and user experience score increased. Next to it, data usage and access control are now newly monitored. After the investments into the new technology services and deductions of project cost, the annual savings are still 70 thousand US dollars.